Diagenetic analysis of tetrapod from the upper triassic, puesto viejo group, Argentina - Previtera, Maria Elena (2016)
The Puesto Viejo Group crops out in the San Rafael Block, southwest Mendoza, Argentina. This group is an important unit for the knowledge theTriassic faunas. It is composed of basal Quebrada de los Fósiles Formation (QF) overlying by the Río Seco de la Quebrada Formation (RSQ). In this study, we report tetrapod remains from the RSQ Formation that includes, until now, exclusively therapsids. Non-mammalian therapsids predominated in terrestrial ecosystems during the Late Paleozoic and Early Mesozoic. Although cynodonts and dicynodonts have been studied from several perspectives, the relation between taxa and sedimentary context has been scarcely documented. This study is aimed to elucidate the diagenesis of tetrapods from the Puesto Viejo Group and its relation to depositional environment. Diagenetic features of therapsid bones from the RSQ Formation were analyzed through thin sections to interpret the degree of taphonomic alteration. Diagenetic processes inferred include substitution; fracturing; brittle deformation and different permineralization events. Combined analyses through scanning electron microscopy; energy-dispersive X-ray spectrometry (SEM-EDX); X-ray diffractometry (XRD) and petrographic studies reveals the substitution of hydroxyapatite by francolite. The presence of fluorine in some samples suggests a link between the elemental composition and depositional environments: floodplain and crevasse splay. Permineralization stages include infilling of vascular canals, trabeculae and fractures with iron oxides and iron carbonate minerals during the burial history. This contribution represents a relevant approach to elucidate the relation between diagenesis on tetrapods and their paleoenvironments, as exemplified in this case study from the Puesto Viejo Group during the Upper Triassic.